Kritični pogled na postopke namestitev na varovani oddelek in odpustov z njega v posebnem socialnovarstvenem zavodu - Škraban, Juš (Socialno delo, 2025)
This article draws on a three-year action research project to transform a secure unit in a special social care institution into community-based services. The article presents the findings of the research, which relate to key aspects of the procedures for admission and discharge from the secure unit. Degradation ceremonies and the almost unchallengeable authority of expert opinion play the key role in the admission process. A relatively low number of discharges is due to factors related to the concept of dangerousness, notion of responsibility, embeddedness of secure unit in the social care system and staff mindset. The author suggests that, in practise, admission to a secure unit can be understood as providing access to care, but that this is (wrongly) conditioned with placement of user. Social work methods provide good grounds for changing the current situation in accordance with human rights and for more productive risk management outside the institution.
Keywords: coercion; človekove pravice; Deinstitucionalizacija; deinstitutionalisation; dezinstitucionalizacija; duševno zdravje; human rights; mental health; prisila; secure units; social work; socialno delo; socialnovarstveni zavodi; varovani oddelki